TINJAUAN POSISI NON-STATE PARTY INDONESIA DAN KEPATUHAN TERHADAP WHO FRAMEWORK CONVENTION ON TOBACCO CONTROL - Pratama, Rama Agung Nur (Justitia et Pax, 2025)
This study aims to analyze Indonesia’s position as a non-State Party to the WHO Framework Convention on Tobacco Control (FCTC) within the framework of international legal politics and to assess the extent to which national health regulations align with the substantive provisions of the FCTC. The research employs a juridical-normative method through literature study, using statutory, conceptual, and comparative approaches. The analysis is based on Miro Cerar’s theory of the relationship between law and politics and the compliance theory. The findings indicate that Indonesia’s decision not to accede to the FCTC reflects the dominance of domestic political considerations, particularly fiscal interests and the tobacco industry, over global public health commitments. Normatively, Law No. 17 of 2023 on Health and Government Regulation No. 28 of 2024 have fulfilled most FCTC provisions to a limited extent and mostly in the health sector, without a whole-of-government approach, particularly in smoke-free areas, packaging and labeling, product control, and cessation services (compliance without ratification). However, significant gaps remain in establishing a multisectoral coordination mechanism, a total ban on advertising, and comprehensive regulation on illicit trade and the environmental impacts of tobacco. At the same time, the study also finds that Indonesia’s implementation of several FCTC provisions cannot be understood merely as discretionary policy choices. While the FCTC itself remains a treaty-based instrument and not a source of customary international law, its widespread ratification and consistent implementation indicate that certain core tobacco control norms reflect emerging international standards and may be regarded as contributing to the formation of customary international law or as expressing general principles of international law related to the protection of the right to health.